Substances that disrupt thyroid hormone biosynthesis (in Romanian) - Pap, Andreea; Moșneang, Crina Laura; Cristina, Romeo Teodor (Medicamentul Veterinar)
Endocrine disrupters are natural or synthetic chemical substances that have the possibility to alter the endocrine functions leading to serious metabolic changes especially in newborns. The accumulation and persistence over long periods of time became a priority in terms of health and environment. The mechanism of action is represented by blocking, mimicking or modifying the effects of thyroid hormones. In this review, the main purpose was to determine what effects have the endocrine disruptors on the thyroid gland, especially on the thyroid hormone biosynthesis and setting the stage involved by it. We focused on the action of perchlorates, phthalates, BPC, PDPEs, soy, isoflavones, nitrates, thiocyanates, bisphenol A and triclorsan and came to the conclusion that their intervention can result in either hyperthyroidism or hypothyroidism.